Dampak Pemekaran Daerah terhadap Pertahanan Negara: Studi Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah - Nora Leylana; Aris Sarjito (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
This qualitative research explores the impact of the expansion of regional autonomy as regulated in Law Number 23 of 2014 concerning the Regional Government on the stability of national defense and security in Indonesia. This background underscores the importance of regional autonomy in shaping the socio-political landscape and its potential impact on national security. Using secondary data analysis, this study explores four main dimensions: the consequences of regional expansion on national stability and security, the dynamics of post-expansion social change, the potential for cross-border conflict and security issues, as well as policy recommendations to mitigate negative impacts and maximize positive impacts on national defense. The findings of this research reveal various insights regarding the various consequences of regional autonomy and highlight the impact of regional autonomy on national defense. The conclusion brings together these findings, emphasizing the need for comprehensive policy adjustments to maintain national security in the face of evolving regional dynamics.